Employee involvement and participation as a function of labor relations and human resource management: Evidence from Greek subsidiaries of multinational companies in the pharmaceutical industry - Eleni Triantafillidou; Theodore Koutroukis (Administrative Sciences, 2022)
Employee involvement and participation is part of Labor Relations and Human Resource Management. This study is to identify how and to what extent employee involvement and employee participation mechanisms are used in the Greek subsidiaries of multinational companies in the pharmaceutical industry. The issues examined in this study are the design of employee involvement and participation practices, the similarities and differences of employee participation practices in the group of companies internationally, corporate employee communication and consultation mechanisms, corporate policy towards trade unions and the EWC nature and agreements. The research method is qualitative with semi-structured interviews conducted with management executives, human resource management executives and the selected organizations participating in the study are active in the pharmaceutical industry and fall within the scope of Directive 2009/38/EC/16.5.2009 on the right of employees to information and consultation at Community-scale companies and groups of companies. The findings indicate that most of the participant companies when designing employee involvement and participation practices, consider a formal model of best practices that has been codified for all multinational companies. Regarding the global company's policy on consultation and employee involvement most of the participant companies state that they provide a little more than the institutional framework requires. Nevertheless, management receives information about the activity and meetings of the EWC systematically at the time of EWC meetings. Increasing employee participation requires both management attention and initiatives on the part of employees.
Keywords: 350; employee participation; Labor Relations; Human Resource Management; European Works Councils